E-procurement in electronic industries - Ong, Lay Pheng. (2008)
Outlines the implementation of an e-procurement process. A detailed study on Gluck, Inc. was conducted, focuseing on Gluck's existing processes, the problems it faced, and the solutions to resolve the shortcomings.